2014
DOI: 10.1111/bju.12637
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the index tumour and tumour volume in prostate cancer using T2‐weighted and diffusion‐weighted magnetic resonance imaging (MRI) alone

Abstract: ObjectiveTo examine the performance of T2-weighted (T2W) and diffusion-weighted (DW) magnetic resonance imaging (MRI) for detecting the index tumour in patients with prostate cancer and to examine the agreement between MRI and histology when assessing tumour volume (TV) and overall tumour burden. Patients and MethodsThe study included 199 consecutive patients with biopsy confirmed prostate cancer randomised to MRI before radical prostatectomy from December 2009 to July 2012. MRI-detected tumours (MRTs) were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(51 citation statements)
references
References 24 publications
6
41
2
2
Order By: Relevance
“…In the 13% of missed index tumours (n = 17), mpMRI missed 47% (n = 8) of high-risk tumours and 53% (n = 9) of low-risk tumours. The sensitivity and specificity of mpMRI detecting index tumours was lower in the present study cohort compared with recent studies, which have reported specificity in detecting index tumours of >90% [17,18]. It seems that not all PCa lesions are detectable on mpMRI (43% [94/220] clinically significant PCa).…”
Section: Discussioncontrasting
confidence: 91%
“…In the 13% of missed index tumours (n = 17), mpMRI missed 47% (n = 8) of high-risk tumours and 53% (n = 9) of low-risk tumours. The sensitivity and specificity of mpMRI detecting index tumours was lower in the present study cohort compared with recent studies, which have reported specificity in detecting index tumours of >90% [17,18]. It seems that not all PCa lesions are detectable on mpMRI (43% [94/220] clinically significant PCa).…”
Section: Discussioncontrasting
confidence: 91%
“…This study demonstrated an overall localization rate for PCa of 56% in ex vivo RP specimens using a combination of T 2 W and DW imaging at 7T. Several other studies that have investigated the performance of in vivo mpMRI using a combination of T 2 W, DW, and dynamic contrast‐enhanced (DCE) imaging at 1.5T or 3T showed higher overall localization rates (64–71%), yet a smaller portion of ≤0.5 cc and/or Gleason score ≤6 cancers was present among their histological findings . Tan et al had comparable histological findings and demonstrated a similar localization rate of 47% using T 2 W‐, DW‐, DCE‐imaging at 3T …”
Section: Discussionsupporting
confidence: 58%
“…Although mpMRI has high performance to rule-in and rule-out clinically significant disease at a regional level, the strategy is not perfect and some relevant cancers might be missed. The issue is even more relevant as the definition of clinically significant disease is debated, and varying the threshold of significance has a substantial impact on the performance of our diagnostic tests (47,48). Also, the high performance reported in the literature comes from high volume expert centers; reproducibility needs to be verified yet.…”
Section: Brachytherapymentioning
confidence: 99%